Performance assessment of agroecology in Attapeu, Lao PDR - Douangsavanh, Sompasith; Xaydala, Viengxay; Chanthalath, Ammala; Dubois, Mark (2024)
This report presents results from WP2 of the Agroecology Initiative . Specifically, this includes an evidence-based assessment of agroecology performance in Attapeu ALL. This utilizes the Holistic Localized Performance Assessment (HOLPA) tool for household surveys, developed by Jones et al. (2024). The HOLPA tool measures the multidimensional performance of agroecological fields, farms, and landscapes to provide an evidence-based understanding of future management and sustainability requirements to support a transition to agroecology.